Eminent domain in the theory of natural law - Rauličkytė, Aušra (Politologija, 1997)
People in the modern state understand inviolability of property rights as a symbol of personal liberty and democratic state. This symbol is an important element of socialisation of political, economic, and legal systems, even though in real life implementation of such a principle is far from its pure and ideal meaning. The right of the state to take private property for public use, or utility, is also presented as a guaranty of safety of private property. Paradoxically, theoretical consolidation of the power of the state was better developed in the political tradition, which rests upon a theory of natural law. According to the theory, people have had natural rights antecedent to government. Government was merely the creation of human consent, established through the mechanism of a universally agreed upon social compact. But there appears philosophical difficulty, because if people in the state of nature that preceded government did not have the right to take private property of another, how could they, then, transfer this power to government? Natural law theorists committed a logical leap and found the right of the state to assume private property to form so much a part of the nature of government, that government would be inconceivable without it. Even more, according to H. Grotius and S. Pufendorf, the private property rights are under the right of the state to take private property. None of these theorists directly analysed why the state has such a right. Conclusion can be drawn that natural law theorists acquiesced the presumption that the state possessed such a power without discussions and arguments. Solidarity in agreement on the existence of the right of the state to take private property without owner’s agreement and on restrictions for implementing this right in different political theories, different states, and different historical periods forces to take seriously the premise about the independent status of this right.